CLASSIFICATION OF LANDSCAPE VOCABULARY IN UZBEK AND ENGLISH - O’rozboyeva Mavluda Shukurlo qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
This article explores the classification of landscape vocabulary in Uzbek and English. It examines how natural features such as mountains, plains, rivers, forests, deserts, and coastal regions are expressed in both languages. The study highlights the semantic similarities and differences between Uzbek and English landscape terms, and emphasizes their role in describing geography, ecology, and the environment. Understanding these words helps learners improve their descriptive abilities and communicate more effectively about the natural world in both languages.